A systematic review and meta-analysis of neuroticism and anxiety during the COVID-19 pandemic - Regzedmaa, Enkhtuvshin; Ganbat, Mandukhai; Sambuunyam, Munkhzul; Tsogoo, Solongo; Radnaa, Otgonbayar; Lkhagvasuren, Nasantsengel; Zuunnast, Khishigsuren (Frontiers in Psychiatry, 2024)
An extensive investigation and meta-analysis were undertaken to learn more about the connection between neuroticism and anxiety during the COVID-19 outbreak. Due to the pandemic's significant effects on the entire world, concerns have been raised about mental health, specifically individual anxiety levels.Neuroticism, a personality trait associated with emotional instability, may have a significant influence on how people respond under these circumstances. 26 papers that looked at the relationship between neuroticism and anxiety in the context of the COVID-19 outbreak were discovered after doing a thorough literature search utilizing the Cochrane Library, HINARI, Google Scholar, and PUBMED. The study has been submitted to PROSPERO under the number CRD42023452418. There has been usage of thorough Comprehensive Meta-Analysis V4 software. Meta-analysis discovered a highly positive relationship between anxiety and neuroticism, which was validated by 26 studies (OR =3.213, 95% CI 2.352 to 4.391).Our findings demonstrate the importance of considering personality traits, notably neuroticism, when assessing psychological responses to a significant global catastrophe like the COVID-19 epidemic. Potential therapies for reducing the consequences of anxiety should be further researched, especially for those with high levels of neuroticism.